Preparasi Kitosan Dari Limbah Udang Windu dan Uji Penurunan Kolesterol pada Kelinci (Oryctolagus cuniculus) secara in vivo - A., Muflihunna; A., Mu’nisa (bionature, 2010)
The study was conducted to examined the effects of chitosan   on cholesterol rabbit under hypercholesterolemic condition. From 100 g chitin of shrimp produce 55 g chitosan. Total of twelve male rabbits were used for this research.Those rabbits were divided into three groups; (K-)) negative control group, (K+) positive (Hypercholesterolemic) group, which were high cholesterol diet for 7 weeks, P1 and P2 preventive groups , same with group B and  supplemented with 5%, 10% chitosan suspension. The results showed that groups which supplemented of chitosan suspension has shown effects on prevent the level of cholesterol,